SMT: An interface for localized storm surge modeling. (February 2016) - Dyer, Tristan; Baugh, John
Highlights: Simulation of engineering designs subject to coastal flooding is computationally expensive. A graphical user interface is presented that employs subdomain modeling to reduce the effort required. Software design and implementation issues that make the approach practical are presented. Novel aspects include an extensible, object-oriented architecture and generalized range search algorithm. Descriptions of the overall methodology and performance results are given, along with a case study. Abstract: The devastation wrought by Hurricanes Katrina (2005), Ike (2008), and Sandy (2012) in recent years continues to underscore the need for better prediction and preparation in the face of storm surge and rising sea levels. Simulations of coastal flooding using physically based hydrodynamic codes like ADCIRC, while very accurate, are also computationally expensive, making them impractical for iterative design scenarios that seek to evaluate a range of countermeasures and possible failure points. We present a graphical user interface that supports local analysis of engineering design alternatives based on an exact reanalysis technique called subdomain modeling, an approach that substantially reduces the computational effort required. This interface, called the Subdomain Modeling Tool (SMT), streamlines the pre- and post-processing requirements of subdomain modeling by allowing modelers to extract regions of interest interactively and by organizing project data on the file system. Software design and implementation issues that make the approach practical, such as a novel range search algorithm, are presented. Descriptions of the overall methodology, software architecture, and performance results are given, along with a case study demonstrating its use.